Comparison Results of Hemoglobin Checkup in Pregnant Women using Cyanmethemoglobin Method and Azidemet Hb Methods - Arif Mulyanto; Fitri Paramitha Annisa; Tantri Analisawati Sudarsono (Biomedika, 2022)
The hemoglobin checkup in pregnant women was done by several methods, some of those were Cyanmethemoglobin and Azidemet Hb methods. The incidence of anemia during pregnancy, childbirth and during the puerperium can be reduced by early detection of anemia by checking hemoglobin levels. The purpose of this study was to determine hemoglobin levels using the Cyanmethemoglobin method and the Azidemet Hb method. Data collection was carried out by observational method using cross sectional design. The research was conducted at the Ajibarang II Public Health Center, Banyumas Regency in October - November 2020. The sample used was 20 respondents. The results of the examination using the Cyanmethemoglobin method for venous blood were 10.12 ± 0.62 g / dL and the Azidemet Hb method for capillary blood was 11.98 ± 1,0009 g/dL. There is a significant difference between the results of hemoglobin examination using the Cyanmethemoglobin method of venous blood and the Azidemet Hb method of capilary blood.